Aplikasi Sistem Pakar Untuk Mendiagnosa Gangguan Kepribadian Pada Remaja Dengan Menggunakan Metode Certainty Factor (CF) - Adi Suwarno; Ishak Husin; Ulfi Elana Zenni (Sekolah Tinggi Teknik - PLN, 2019)
Adolescence is a period of increased activity, maturity of sexuality, growth of awareness, and recognition that the time free from problems experienced in childhood is lost forever. So they experience emotional instability as a result of adjusting themselves to new patterns of behavior and social environment. Personality and behavior disorders in adolescents are problems faced by parents and their environment. In this study, this knowledge was obtained from experts, namely psychologists. This study uses an interview method with a Psychologist. The expert system is a system designed to assist in detecting diseases with a dynamic knowledge base. This expert system can deduce the user's illness based on the symptoms of adolescent personality disorders that are entered into the system. As for the purpose of the research is to produce an expert system to assist psychologists in documenting their knowledge. The expert system will display the amount of confidence the symptom has on the possibility of the user's illness. The amount of the trust value is the result of calculations using the Certainty Factor (CF) method. The results obtained from this study are the application of an expert system to diagnose adolescent personality disorders with the certainty factor method by using a computer as a tool to access data Teenagers, Adolescent Personality Disorders, Expert System, Certainty Factor